PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA MAKARONI NGEHE CABANG JOMBANG TANGERANG SELATAN - Reisha Darellin; Purwanti (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of service quality and price on consumer satisfaction at Makaroni Ngehe, Jombang Branch, South Tangerang, both partially and simultaneously. The method used in this study is the associative quantitative method. The population in this study was 15,854 people during the period of 2024. The sampling technique used the Slovin formula, so that a sample of 97 respondents was obtained. Data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results of the study partially showed that service quality had a significant effect on consumer satisfaction, with the regression equation Y = 1.130 + 0.495X1. The results of the hypothesis test showed that the calculated t value> t table (9.739> 1.985), so H0 was rejected and Ha was accepted, which means that there is a significant effect between service quality and consumer satisfaction. The price variable also has a significant effect on consumer satisfaction, with the regression equation Y = 1.130 + 0.481X2. Hypothesis testing shows that t count > t table (9.861 > 1.985), so H0 is rejected and Ha is accepted. Simultaneously, service quality and price have a significant effect on consumer satisfaction, with the regression equation Y = 1.130 + 0.495X1 + 0.481X2. The results of the F test show that F count > F table (69.456 > 3.093), so H0 is rejected and Ha is accepted. This means that there is a significant simultaneous effect between service quality and price on consumer satisfaction.